2018
DOI: 10.1080/2158379x.2018.1468151
|View full text |Cite
|
Sign up to set email alerts
|

Authority as epistemic capital

Abstract: The article proposes that authority denotes an actor's appeals or other references to objects or facts that she expects others to respect or fear. The paper identifies four types of authority: capacity-based, ontological, moral, and charismatic. That is, authority can be built on the assumption that an actor is capable of accomplishing things; on expertise or respected accounts of reality; on deference to principles; and on extraordinary awe attached to an organization or individual. Such authority can be call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…In their attempts to exert influence, speakers construct and appeal to facts, principles or entities that they assume others deem unavoidable determinants of the situation, or they cite sources assumed to lend credibility to the claims and proposals made. In other words, actors wishing to influence lean on others' authority by referring to them: by presenting a framing of reality that utilizes authoritative views and actors (Alasuutari, 2018).…”
Section: Ios and National Policy-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…In their attempts to exert influence, speakers construct and appeal to facts, principles or entities that they assume others deem unavoidable determinants of the situation, or they cite sources assumed to lend credibility to the claims and proposals made. In other words, actors wishing to influence lean on others' authority by referring to them: by presenting a framing of reality that utilizes authoritative views and actors (Alasuutari, 2018).…”
Section: Ios and National Policy-makingmentioning
confidence: 99%
“…It denotes the recognition among the actors of someone or something worthy of note when considering one's own conduct. This means that actors may present themselves as powerful or claim authority for themselves, but they may also make use of authorities and authoritative principles, thus struggling for a hegemonic conception of the situation that significantly affects others' views and behaviour (Alasuutari, 2018). Such exerting of influence is referred to as epistemic governance because it functions through knowledge and its validation (Alasuutari & Qadir, 2014).…”
Section: Ios and National Policy-makingmentioning
confidence: 99%
“…Beyond variation in the supply and institutionalized form of policy advice, the cultural meanings attached to different types of organizations are also important. Earlier epistemic governance research has argued that actors wishing to influence national policy‐making creatively refer in their argumentation to all available actors, facts and values considered authoritative by the target audience, thus amassing epistemic authority for the projects they seek to promote (Alasuutari, 2018; Alasuutari et al., 2016). Studies on parliamentary debates have observed some variation between national contexts in terms of which actors are deemed most legitimate in political reassurance work (Tiaynen‐Qadir et al., 2019; Vähä‐Savo, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In their attempts to convince others of their arguments, actors engaged in policy‐making routinely appeal to facts, principles, and authorities that they believe lend credibility to their positions (Alasuutari & Qadir, 2019 ). In epistemic governance framework, authority refers to ‘anything that actors use to affect others; it denotes the recognition among the actors of someone or something being worth taking into account when considering one's own conduct’ (Alasuutari, 2018, p. 167). Although organizations are major source of readily available information and policy recommendations (Rautalin et al., 2021), no studies have examined how organizations in general are invoked as scientific authorities in the political debates over new legislation.…”
Section: Epistemic Governance Perspective On Authority Of Organizationsmentioning
confidence: 99%
“…Authority and power are relational concepts. Authority is dependent on and consists of recognition by others (Alasuutari, 2018). In policy networks, each participant's authority thus depends on how other participants see it.…”
Section: Communicating Political Power: Authority Performances Based On Validity Claimsmentioning
confidence: 99%